Codon optimization of the prM-E coding region generates stable genome-length cDNA clone for a chimeric dengue 2/3 virus that can be propagated in Escherichia coli - Keelapang, Poonsook; Yasom, Sakawdaurn; Puttikhunt, Chunya; Ketloy, Chutithorn; Sittisombut, Nopporn (Biomedical Sciences and Clinical Medicine, 2017)
Abstract In an effort to generate a chimeric dengue virus containing the prM-E sequence from DENV-3 and with the rest of the viral genome derived from a DENV-2 strain 16681-3pm by in vitro ligation of subgenomic fragments, it was found that the ligated chimeric genome could not be stably propagated as genome-length cDNA clone in Escherichia coli. Native DENV-3 prM-E coding region may contain certain nucleotide sequence that results in plasmid instability when ampli fi ed in E. coli. In this study, we modi fi ed codons in the DENV-3 viral sequence into those that are most frequently used in human genome. Employing the Gibson assembly method, the modi fi ed prM-E fragment was introduced into the full-length cDNA clone of strain 16681-3pm to replace the corresponding sequence in a DENV-2 genome. The full-length plasmid cDNA clone intended for the generation of a chimeric virus, D3 prMEopt/16661-3pm, was successfully propagated in E. coli. In vitro transcription of this clone produced full-length RNA transcripts that generated infectious viruses when introduced into cultured mammalian cells. Based on kinetics experiments, the replication of D3 prMEopt/16661-3pm with modi fi ed codons in the prM-E gene was comparable to the one generated by the in vitro ligation approach. By combining the use of modi fi ed codons and the Gibson assembly method, a full-length cDNA clone of a chimeric virus containing the DENV-3 prM-E sequence can be stably propagated in E. coli, facilitating further manipulation of the viral sequences. Availability of such an infectious cDNA clone would provide a valuable tool for investigating the role of nucleotide/amino acid variations in the DENV-3 prM-E gene in viral replication, immunogenicity, and pathogenicity as well as accelerating dengue vaccine development.